Growth and Yields of Bima Brebes Shallot Variety Planted Using A Floating Hydroponics System - Chiska Nova Harsela (Eduvest - Journal of Universal Studies, 2023)
Shallots are a horticultural crop that has an important meaning for the community, so in Indonesia there are various methods of utilizing narrow land as an empowerment effort in growing shallots, one of which is by means of hydroponics. Hydroponics has various types, one of which is the floating hydroponics system. This study aims to determine the growth and yield of shallot plants of the Bima Brebes variety grown using the floating hydroponics system. This research uses a qualitative approach with the Miles and Huberman interactive data analysis model which consists of 3 main things: data reduction, data presentation, and conclusion drawing. Meanwhile, data collection used documentation techniques to collect journals with the keywords shallot and floating hydroponics system from various sources. The results showed that shallots have high economic value and complete nutritional content, making it an important vegetable commodity for the community. The Bima Brebes shallot variety is very suitable for planting with this method because it has good characteristics. By using the right tools and materials, the growth of shallots of the Bima Brebes variety can be successfully implemented in a floating hydroponic system.